Analysis of accounting of financial expenses in the process of financial planning of transport companies - Shiryaeva, Ludmila; Khotyeyeva, Natalia; Chiz, Ludmila; Bondarenko, Veronika (Technology audit and production reserves, 2017)
The object of research is practical aspects of financial planning of transport companies. Factors affecting the parameters of the process of financing capital-intensive companies are analyzed, which include port and shipping companies. Structural changes in the economy and the financial system led to both a lack of financial resources in the market at an optimal price, and to reluctance of financial intermediaries to finance the activities of companies with a heavy asset structure. The level of competition on the one hand requires a reduction in costs, on the other hand, technical modernization, as a result, financial planning must be made more flexible. The conditions in the financial markets are considered to attract additional financing primarily for shipping companies. Changes in financing conditions need to be taken into account in the financial planning process, primarily the level of financial costs and the level of risk in budgeting, providing for an alternative way of financing. In some cases it is advisable to refuse to attract, as the effect of financial leverage can be negative. The study of trends in terms of development of capital raising allows to more accurately predict the level of efficiency of using the company’s capital.